Ð”ÐµÐ¹ÑÑ‚Ð²Ð¸Ðµ ÑÐºÑÑ‚Ñ€Ð°ÐºÑ‚Ð¾Ð² Ð¸Ð· ÑÐ¼Ð±Ñ€Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ñ‹Ñ… Ñ‚ÐºÐ°Ð½ÐµÐ¹ ÐºÑƒÑ€ Ð½Ð° Ð¼Ñ‹ÑˆÐµÐ¹ Ñ ÑÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ð¾Ð¹ Ð»ÐµÐ¹ÐºÐ¾Ð¿ÐµÐ½Ð¸ÐµÐ¹ - Kuznetsova, V. G.; Zhegunov, G. F. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The effect of extracts derived from embryonic tissues of chickens on mice with experimental leucopenia was studied. The recovery of the number of blood leucocytes even at the first 24 hrs after their introduction was observed. It has been found that cryoextracts possessed more manifested and prolonged effect versus the ones non-frozen.